OUTSOURCING OF LABOUR AS AN OBSTRUCTION TO WELFARE - Diangsa Wagian, M. Yazid Fathoni & (Jurnal IUS (Kajian Hukum dan Keadilan), 2014)
Act Number 13 of 1999 concerning Employment provide for company to perform management efficiency and financial efficiency by outsourcing employment system. In contrast with developed countries, outsourcing in Indonesia, based on Act Number 13 of 1999, intended not to find workers who have specially expertise or specially ability, but to find worker to fill non core business job category in the company or activities not directly related to the production processKey word: outsourcing, workers, protection